Implementing a Student-Centered Pedagogy: Doing so in the Indonesian Teaching-Learning Context - Hanung Triyoko (Register Journal, 2012)
Today’s educators must be willing to shift from the teacher-centered paradigm, which was in place when they themselves were students, to the new paradigm of student-centered education. This article was inspired by the challenges and opportunities experienced by the writers while attempting to  implement a student-centered pedagogy. We will share some of our experiences as educators to provide a context for various aspects of student centered-learning.  Understanding some of the successes and failures we have experienced in our careers may help to highlight the potential and importance of student-centered pedagogy in its many facets. Based on the vignettes from our teaching experiences, we have identified four major ideas about how to adopt a more student-centered approach: planning lessons that encourage student interest; adapting the curriculum to meet student’s needs; using technology in the classroom; and developing mutually respectful relationships. Keywords : Student-Centered Pedagogy; Student’s Interest, Student’s Needs; Mutually Respectful Relationships